Produkcja biowodoru w procesach biologicznych = Production of biohydrogen in biological processes - Suchowska-Kisielewicz, Monika; Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Studies carried out over the past two decades, gives a promising perspective biohydrogen production. However in terms of economy process its efficiency must be significantly increased. A current research goal should be to find new methods of recovery of hydrogen from organic substrates at the highest level. Biohydrogen production by fermentation is the most frequently indicated as the most effective method.
Keywords: produkcja biowodoru; fermentacja; biofotoliza; fotosynteza anoksygenowa; biohydrogen production; fermentation; biophotolysis; photosynthesis